An unusual case of primary intrascrotal lipoma - Andrea Fabiani (Archivio Italiano di Urologia e Andrologia, 2016)
In daily clinical practice, intrascrotal lesion are commonly detected, both by clinical examination either by ultrasound scan. While 95% of testicular lesions are malignant, most paratesticular lesions are benign. Among these, intrascrotal lipomas must be take into account in differential diagnosis. When they originate from scrotal wall, they named “primary scrotal lipoma”. We describe a case of a primary intrascrotal lipoma diagnosed after surgical excision in a young man presented at our Urological Department complaining a painful left scrotal mass.